Status Report Planning Commission 1984 - Planning Commission (Planning Commission, 1984)
The Integrated Rural Energy Pilot Programme which was started under the National Rural Energy Planning Exercise in 1981 has now entered the fourth year. The experience from this exercise is being utilised to prepare a full fledged IREP programme for all the States during the Seventh Plan.
Rural Energy Division Planning Commission
Rural Energy Division Planning Commission